Assessment of Quality of Life in a Sample of Iraqi Patients with Psoriasis. - H. Abdulridha, Sarah; J. Kadhim, Dheyaa; A. Abdul Razzak, Sarmad (Iraqi Journal of Pharmaceutical Sciences, 2020)
Psoriasis is a dermatological, chronic, immune-mediated condition. Psoriasis symptoms are not associated with physical burden only, but it may also have psychosocial effects on patients, diminished cognitive control, poor body image and impairments in everyday life. The value of quality of life is important since improving it is the principal goal for non-curative disease. The aim of the current study was to evaluate quality of life in a sample of Iraqi patients with psoriasis. This study is a cross-sectional study that involved 300 already diagnosed psoriasis patients who attended to the center of Dermatology and Venereology, Medical City/Baghdad. The mean age of patients was (35.156 ±10.549 years). The Arabic version of Dermatology Life Quality Index was used to assess quality of life. The mean total score is 11.29± 5.45 and the majority of the patients (53.7%) had a total score of more than 10, which indicates a significant deterioration in patients’ quality of life. The greatest impact was found in symptoms and feelings (mean = 1.66 ± 0.75) while the lowest impact was noted in personal relationships (0.51± 0.65). Increasing age and monthly income as well as vulgaris type of psoriasis associated significantly better quality of life. While Psoriasis Area and Severity Index associated significantly worse quality of life. In conclusion, psoriasis exerts significant, negative impact on patients’ quality of life, especially among those with younger age, lower monthly income, high disease activity, and types of psoriasis other than vulgaris.